Iron Deficiency and Athletic Performance in Endurance Disciplines: A Scoping Review - Król, Maria; Patalong, Mikołaj; Błaszkowski, Bartłomiej; Kołodziej, Przemysław; Czapliński, Mieszko; Szplit, Ewa; Michnowska, Wiktoria; Pustuła, Paweł; Kubicki , Mateusz; Cemaga, Roman (Quality in Sport, 2026)
Background: Iron deficiency is one of the most common nutritional deficiencies in athletes and is particularly prevalent in endurance disciplines. Even without anemia, reduced iron availability may impair aerobic performance, increase fatigue, and affect training adaptation. Objective: This scoping review aimed to evaluate the impact of iron deficiency, with or without anemia, on athletic performance and fatigue in endurance athletes. Methods: A literature search was conducted in PubMed and Google Scholar. Peer-reviewed studies published in English between 2000 and 2026 were included. Eligible studies assessed iron status in endurance athletes in relation to performance, fatigue, or exercise-induced changes in iron metabolism. Studies involving non-athletic populations, children or adolescents, animal models, and case reports were excluded. Results: Iron deficiency was consistently reported as highly prevalent among endurance athletes, particularly females. Athletes with depleted iron stores frequently demonstrated reduced aerobic capacity, lower VO₂peak, and increased fatigue, even in the absence of anemia. Exercise-induced elevations in hepcidin were commonly observed, especially during periods of intensified training, potentially limiting iron absorption and availability. Iron supplementation was associated with improvements in aerobic performance and fatigue in iron-deficient athletes, particularly when baseline ferritin levels were low. Conclusion: Iron deficiency is a clinically relevant condition in endurance athletes and may impair performance and increase fatigue even without anemia. Regular monitoring of iron status and individualized management strategies are essential to support health and performance in endurance sports.